Volume 1: Advanced Energy Systems; Advanced and Digital Manufacturing; Advanced Materials; Aerospace 2008
DOI: 10.1115/esda2008-59199
|View full text |Cite
|
Sign up to set email alerts
|

3D Multi-Scale Topography Analysis in Specifying Quality of Honed Surfaces

Abstract: The quality of the surface texture on cylinder liners of engines has an important influence on oil consumption and running performance. This texture is generated with a succession of three honing operations (rough, finishing and plateau honing). These honing steps are difficult to optimize due to the large number of process variables (Velocity of the rotational motion, velocity of the axial motion ...) and their complex interrelation. This paper discusses the use of the multiscale topographic parameter of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Finally, the impact of the dynamics on the surface appearance of surfaces obtained after the plateau honing stage on cylinder no. 1 will be investigated with the 3D multiscale analysis [11].…”
Section: Experiments Detailsmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, the impact of the dynamics on the surface appearance of surfaces obtained after the plateau honing stage on cylinder no. 1 will be investigated with the 3D multiscale analysis [11].…”
Section: Experiments Detailsmentioning
confidence: 99%
“…Low inversion acceleration of the stroke motion leads to traces of horizontal grooves with α close to zero at the base and top of the cylinder liner. In order to study the quality of the texture obtained through honing, the method developed by Sabri et al [11], was implemented. The frequential breakdown of the surface topography in 3D leads to the identification of four digital criteria: the cross angle of the groove, the angle of the grooves (left or right), the groove density and the m-turn criterion.…”
Section: Impact On the Texture Obtainedmentioning
confidence: 99%
See 2 more Smart Citations
“…As described by Sabri et al [97], some engine parts, such as cylinder liners, have a value for their honed surfaces like an Rpk parameter around 0.3-0.5 µm, an Rk around 1 µm, and an Rvk around 1-1.5 µm. They reported that some manufactures in the automotive industry, such as Renault or PSA Citroen, introduced other parameters describing the functionality parameters, such as Cr (Running-in criterion), Cf (operating criterion), and Cl (lubricating criterion).…”
Section: Effect Of Honing Parameters On Surface Roughnessmentioning
confidence: 99%